CERIF tutorial: Part 1 - Dvořák, Jan (2018)
CERIF is an EU recommendation to member states and the European Commission (EC) has authorisedeuroCRIS to maintainand develop CERIF and its usage. CERIF base entities: OrgUnit, person, project